Development of a Live Recombinant BCG Expressing Human Immunodeficiency Virus Type 1 (HIV-1) Gag Using a pMyong2 Vector System: Potential Use As a Novel HIV-1 Vaccine - Kim, Byoung-Jun; Kim, Bo-Ram; Kook, Yoon-Hoh; Kim, Bum-Joon (Frontiers in Immunology, 2018)
Even though the rate of new HIV-1 infections is gradually decreasing worldwide, an effective preventive vaccine for HIV-1 is still urgently needed. The recombinant Mycobacterium bovis BCG (rBCG) is promising for the development of an HIV-1 vaccine. Recently, we showed that a recombinant Mycobacterium smegmatis expressing HIV-1 gag in a pMyong2 vector system (rSmeg-pMyong2-p24) increased the efficacy of a vaccine against HIV-1 in mice. Here, we evaluated the potential of an rBCG expressing HIV-1 p24 antigen Gag in pMyong2 (rBCG-pMyong2-p24) in a vaccine application for HIV-1 infection. We found that rBCG-pMyong2-p24 elicited an enhanced HIV-1 p24 Gag expression in rBCG and infected antigen presenting cells (APCs). We also found that compared to rBCG-pAL-p24 in a pAL5000 derived vector system, rBCG-pMyong2-p24 elicited enhanced p24 specific immune responses in vaccinated mice as evidenced by higher levels of HIV-1 Gag-specific CD4 and CD8 T lymphocyte proliferation, gamma interferon ELISPOT cell induction, antibody production and cytotoxic T cell (CTL) responses. Furthermore, rBCG-pMyong2-p24 showed a higher level of p24-specific Ab production than rSmeg-pMyong2-p24 in the same pMyong2 vector system. In conclusion, our data indicated that a live recombinant BCG expressing HIV-1 Gag using a pMyong2 vector system, rBCG-pMyong2-p24 elicited an enhanced immune response against HIV-1 infections in a mouse model system. So, rBCG-pMyong2-p24 may have the potential as a prime vaccine in a heterologous prime-boost vaccine strategy for HIV-1 infection.